Avaliação do desempenho das propriedades mecânicas de concretos self compacting elaborados com diferentes tipos de cimentos submetidos à cura térmica - Santos, L.f. [UNESP]; Barbosa, M.p. [UNESP] (IBRACON - Instituto Brasileiro do Concreto, 2011)
Steam curing is one of the mechanisms used in the precast industry to accelerate the strength gain of structural elements. The values of temperature and time of ideal cures for this strength gain vary with the cement and mix design used in concrete. Little is known about the behavior of self-compacting concrete (SCC) when subjected to the steam accelerated curing process, especially with regards to its mechanical properties. This article evaluates the compressive strength of two mixture designs of self-compacting concrete class 40 MPa with two different cements, cement CP III 40-RS and CP II E-32 submitted to normal curing (I accordance with NBR 5738:2003 [2] and to steam curing. Two different steam curing temperatures were used, at 65°C and 80°C and three curing cycles, 4 h, 6 h and 8 h. The study was done at the Laboratory of Civil Engineering CESP - LCEC - Ilha Solteira/SP, where concretes with specimen cylinders of 10 cm x 20 cm were tested. The compressive strengths were obtained at the end of the steam curing plateau (called immediate strength to the cycle) and at ages 3, 7, 28, 56 and 91 days (called strength at advanced ages) and for concrete subjected to normal curing, the ages of rupture were performed at 3, 7, 28, 56 and 91 days. An analysis of the correlation was performed between the values of rupture of the concrete subjected to normal cure, with the values of immediate strength to the cycle and also to the strength at advanced ages. The benchmarks were performed according to the type of cement used, curing temperature and time in the steam curing plateau. Overall, the results show that the concrete with cement CP II E-32 at 65 ºC, for the steam curing plateau of 4 hours, was the best compressive strength value when subjected to these curing conditions, while the concrete with cement CP III 40-RS at 65 °C, for 6 hours of steam curing plateau, was the optimum strength value.

A cura térmica a vapor é um dos mecanismos utilizados na indústria de pré-moldados para acelerar o ganho da resistência dos elementos estruturais. Os valores de temperatura e tempos de cura ideais para ocorrer esse ganho de resistência variam conforme o cimento e o traço utilizado no concreto. Pouco se conhece sobre o comportamento do concreto auto-adensável (CAA) quando submetido ao processo de cura acelerada a vapor, principalmente em relação as suas propriedades mecânicas. O presente artigo avalia a resistência a compressão de duas composições de concreto auto-adensáveis de classe 40 MPa elaborados com cimentos distintos, cimento CP III 40-RS e cimento CP II E-32 submetidos à cura normal (de acordo com a NBR 5738:2003 ([2]) e à cura térmica a vapor. Foram utilizadas duas temperaturas de cura térmica distintas, 65°C e 80°C e, três patamares isotérmicos, 4 h, 6 h e 8 h. O estudo foi feito no Laboratório CESP de Engenharia Civil - LCEC - Ilha Solteira/SP, onde foram ensaiados corpos-de-prova cilíndricos de 10 cm x 20 cm. As resistências à compressão foram obtidas ao fim do patamar de cura térmica a vapor (denominada resistência imediata ao ciclo) e nas idades de 3, 7, 28, 56 e 91 dias (denominadas resistências nas idades avançadas) e, para os concretos submetidos à cura normal, as idades de ruptura foram realizadas com 3, 7, 28, 56 e 91 dias. Foram feitas análises de correlação entre os valores de ruptura dos concretos submetidos à cura normal com os valores de resistência imediata ao ciclo e também para as resistências nas idades avançadas. As análises comparativas foram realizadas em função do tipo de cimento empregado, temperatura de cura e tempo no patamar isotérmico. Os resultados encontrados mostram que em termos globais, o concreto com cimento CP II E-32 apresentou a 65ºC, para o patamar isotérmico de 4 horas o melhor valor de resistência a compressão quando submetido a estas condições de cura, enquanto que o concreto com cimento CP III 40-RS apresentou a 65ºC, para o patamar isotérmico de 6 horas o melhor valor de resistência.
Performance evaluation of mechanical properties of self-compacting concrete prepared with different cements types submitted to steam curing
Keywords: concreto auto-adensável; resistência à compressão; cura térmica à vapor; temperatura de cura; patamar isotérmico; self-compacting concrete; compressive strength; steam curing; curing temperature; isothermal plateau